(untitled) (Singaporean Journal of Business Economics and Management, 2021)
With ecological problems deteriorating, customers’ concerns regarding ecological protection have prompted the enhancement in consumer purchasing approach towards a green way of life. Subsequently, green marketing and the development of green products are valuable strategies that are utilized by firms to increment upper hands and have a possibility of acquiring the fulfillment of consumers to accomplish the company’s main goal and vision. Green marketing and the development of green products have different advantages to firms as far as expanding the economical environmental advantages and building the familiarity with the company’s brand. This paper portrays the significance of green marketing and the role it plays in consumer behavior by using content analysis as the methodology. This study initially carries out a comprehensive literature review regarding green marketing dimensions, like green packaging, branding. pricing, and such. The results of this paper ascertain the significance of green marketing based on the findings of other studies and concludes the indispensability of a green marketing strategy for firms.